Germination Dynamics of Acacia Species Driven by Soil Type and Pre Sowing Soaking of Seed for Nursery Raising - Haq, Ejaz ul; Qazi, Imran; Safeer Uddin; Muhammad Waqas; Muhammad Nadeem; Khan, Muhammad Idrees; Saleem, Ashiq; Ahmad, Ijaz (Indus Journal of Bioscience Research, 2024)
Development of seedlings is a common barrier in dry lands is due lack of awareness about seed biology and germination of valued species in dry climates leads to poor specie germination performances. The effects of seed soaking times and soil types on germination at the nursery level received very little attention in the literature so far. The germination of seeds of two acacia species (Acacia nilotica and Acacia modesta) have been studied to determine variances in germination. The results confirmed that A. nilotica germination performance was best in clay soil without soaking (0HRS), which was tailed by 12HRS soaking of seed. Interestingly, in sandy soil, the germination rate was favored by 36HRS soaking followed by 24HRS seed soaking whereas minimum germination was observed in control (0HRS). Although A. modesta seed germination performance was best observed at 36HRS soaking timing in both soil types followed by 24HRS, 12HRS and untreated seed (Control) respectively. Our study's findings hold significance for restoration bodies that are concerned with improving germination in dry regions for rehabilitation and transplantation. A. nilotica nursery can easily be developed in clay soil. Based on the observations it is recommended that seeds of A. nilotica nursery should be grown directly in clay soil whereas the seeds require pre-sowing soaking for sandy soil. A. modesta is of different nature and need soaking prior to sowing for at least 36 and 24HRS in both soil types.